The stock market course - Fontanills, George; Gentile, Tom, 1965- (Wiley, 2001)
The Stock Market Course arms you with the basic knowledge and skills you need to realize your dreams of success as a stock trader. In easy-to-understand terms, George Fontanills and Tom Gentile familiarize you with the ins and outs of the markets - their history, mechanics, and rules. They clearly explain all key stock market terms and procedures, assess the relative risks and benefits of stock investment, and even help you to determine whether or not you are suited financially and psychologically to be a market player.